2001
DOI: 10.1086/320182
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Prevalence of Strains Expressing an Extended‐Spectrum β‐Lactamase Phenotype and Characterization of Isolates from Europe, the Americas, and the Western Pacific Region

Abstract: To evaluate the prevalence of extended-spectrum beta-lactamase (ESBL)-producing strains among species of Enterobacteriaceae, a microdilution susceptibility test was performed with strains of Klebsiella pneumoniae, Escherichia coli, Proteus mirabilis, and Salmonella species that were isolated as part of the SENTRY project. The highest percentage of ESBL phenotype (defined as a minimum inhibitory concentration [MIC] > or =2 microg/mL for ceftazidime, ceftriaxone, or aztreonam) was detected among K. pneumoniae st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
274
9
25

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(341 citation statements)
references
References 22 publications
33
274
9
25
Order By: Relevance
“…These findings are in concordance with the studies conducted by other authors, who also reported a rate of 100% sensitivity to imipenam [31][32][33][34][35]. These carbapenam agents may be beneficial in treatment of AmpC infection; however, indiscriminate use of these agents may promote increased resistance to carbapenam.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in concordance with the studies conducted by other authors, who also reported a rate of 100% sensitivity to imipenam [31][32][33][34][35]. These carbapenam agents may be beneficial in treatment of AmpC infection; however, indiscriminate use of these agents may promote increased resistance to carbapenam.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of ESBL-producing Salmonella was about 17 % with a higher proportion (73 %) of these attributable to isolates from Kuwait. This prevalence is much higher than any reported prevalence rates in Salmonella spp., such as the prevalence of 1.5 % reported in the Taiwan (Li et al, 2005;Su et al, 2005), 1.9 % in the USA (Dunne et al, 2000), 2.4 % in Latin America (Winokur et al, 2001), 0.8 % in Europe and 3.4 % in the Western Pacific region (Winokur et al, 2001). The reason for the high prevalence of ESBL-producing Salmonella in our study may be related to the level of usage of the drug in the community, although we do not have any quantitative data on this.…”
Section: Discussionmentioning
confidence: 99%
“…b-Lactamases are the predominant (Arlet et al, 2006). In 2004, Salmonella resistant to extended-spectrum cephalosporins were identified in 43 countries encompassing Europe, Latin America, the USA, Taiwan and the Western Pacific (Winokur et al, 2001;Dunne et al, 2000;Li et al, 2005;Su et al, 2005), and its prevalence ranged between 0 and 3.4 %. This is believed to be the first report of CTX-M type ESBLproducing Salmonella in Kuwait and the UAE, and one of the very few reports on the ESBL-producing Salmonella in the Middle East (Hammami et al, 1991;Moubareck et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, ESBL production has been identified worldwide in a number of different organisms, including K. pneumoniae, E. coli, Proteus mirabilis, and Salmonella species (8)(9)(10)(11). ESBL-producing Salmonella species are rare but have increased worldwide due to the abuse of β-lactams; the reported prevalence in western Pacific nations is 3.4% (8,(12)(13)(14). CTX-M-type β-lactamase is one of the most common ESBLs (15).…”
Section: Introductionmentioning
confidence: 99%